Marketing knowledge management and its role in developing marketing performance (Journal of Humanities and Social Sciences Research, 2023)
Marketing knowledge management is a strategic and competitive element, due to the role it plays in the success of companies and their transformation towards the knowledge economy as well as its role in enabling companies to face the intensity of competition, the study aimed to shed light on the role of marketing knowledge management in developing marketing performance in the General Company for Vegetable Oil Industry Iraq, as the management of marketing knowledge is one of the important elements to ensure the company continues to operate, grow and develop in the dynamic Environment in which it operates, due to the great role it plays in enhancing its ability to develop, grow and develop in the dynamic innovation of immigrants and immigrants in which it operates, due to the great role it plays with companies with enhancing its earnings with earnings to develop new and immigrants with earnings and immigrants in developing companies and immigrants in which it operates are due to the great roles it will earn by companies in enhancing its earnings with earnings with earnings and profits with earnings of businesses and immigrants in developing new and immigrants in developing companies and immigrants in which it engage in businesses. To achieve this, the research relied on the analysis of the variables on the questionnaire as a main tool for collecting data and information. The applied results have shown that there is a significant and positive effect of marketing knowledge management on marketing performance, and this is a good indication of the influence of marketing knowledge management in developing the marketing performance of the research sample company.